IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL): ANALISIS KESESUAIAN PROGRAM, ORGANISASI, DAN MASYARAKAT DI KOTA SAMARINDA - Rezidan Tries Irwahyudi; Ayu Dewi Mayasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The Comprehensive Systematic Land Registration Program (PTSL) is a government policy aimed at providing legal certainty regarding land ownership through systematic and comprehensive land registration activities. This study aims to analyze the implementation of the PTSL Program at the National Land Agency (BPN) in Samarinda City based on David C. Korten’s theory of policy implementation, which emphasizes alignment between the program, the implementing organization, and the beneficiary community. This study employs a qualitative descriptive method with data collection techniques including observation, interviews, documentation, and literature review. The results indicate that the implementation of the PTSL Program in Samarinda City has proceeded fairly well and has yielded benefits such as legal certainty regarding land ownership, an increased sense of security, and support for the appreciation of land’s economic value. From a program perspective, the implementation of PTSL has aligned with the program’s primary objectives. From the perspective of the implementing organization, the Samarinda City BPN has carried out its duties and functions well, although it still faces limitations in human resources and technical constraints. From the community’s perspective, the program has received a positive response and a fairly high level of participation. However, there are still obstacles, such as the community’s limited understanding of program procedures, incomplete administrative documents, and issues related to land measurement and boundaries.Keywords: Policy Implementation, PTSL, BPN, Land Legal Certainty